Rancang Bangun Sensor Kelembaban Udara menggunakan Plastic Optical Fiber (POF) dengan Cladding TiO2-SiO2 dan Data Transmisi: Febrielviyanti, Harmadi, Dahyunir Dahlan, Yetria Rilda - Febrielviyanti Febrielviyanti; Harmadi Harmadi; Dahyunir Dahlan Dahyunir Dahlan; Yetria Rilda Yetria Rilda (Jurnal Fisika dan Aplikasinya, 2019)
The optical fiber is a transmission medium in the form of a cable made of glass or plastic used to transmit light signals from one point to another. The working principle of optical fibers utilizes the principle of perfect reflection by utilizing the refractive index difference between the core and cladding. The optical fiber can be used as a sensor by using an instrumentation system consisting of input, process, and output. Input or input uses a diode laser, where the spectrum is very narrow so it is suitable to be used as a source. The data transmission process uses optical fiber as a waveguide. Data recording transmits humidity using Arduino Uno and Ethernet Shield. The output is in the form of output voltage displayed on the LCD or PC. The best stripping length is 2 cm with TiO2-SiO2 coating as a substitute for cladding, which shows the value of R2 = 0.982. The average error obtained from the design of air humidity devices was 3.06%. This shows the incompatibility between reading a tool designed with a standard measuring instrument because the sensor designed is still very vulnerable to systematic errors.